(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The circular -distance between nodes of a graph is obtained by the sum of detour -distance and -distance. The average circular -distance between the nodes of a graph is the sum of average of the detour -distance and -distances. In this paper, we deal with the average circular -distance between nodes of graph. We compute the relation between circular Wiener index and circular -Wiener index of -regular graphs. We obtained results on circular -Wiener index of some special graphs